The Effect of Sex Education on Knowledge and Attitude in Adolescent with Intellectual Dissability in SLB N 1 Bantul - Widyaningrum, Rahmah; Siwi, Ignasia Nila (Universitas STRADA Indonesia, 2018)
Background: There are 3.708 children with intellectual dissability in Yogyakarta. Adolescents with intellectual disability will have limitation on cognitive, adaptive behavior and social-personal function, which lead to some diverted behaviors such as inability to maintain cleanliness, taking care of themselves, and conducting good act of sexual behaviors. These conditions will lead to social perception as childish, inhuman, asexual, or bad sexual behavior due to lack of information and low cognitive function. Purpose : This study aimed to assess the efect of sex education on knowledge and attitude of adolescent student with intellectual dissability in SLB N 1 Bantul, Yogyakarta. Methods : This is a pre experimental with one group pre test-post test design. Twenty (20) students with intellectual dissability were recruited using simple random sampling. Knowledge and attitude were measured using questionnaire before and after sex education program for four weeks. The data were analyzed using paired t-test. Result : There is a significant (p= 0.000) different on the knowledge anda significant (p= 0.039) different on the attitude before and after six-sex education program. Conclusion : Adolescent with intellectual dissability require specific treatment, communication and skillto improve their knowledge and attitudethrough sex education program.